'Don't bother with that': the use of negative imperative directives for defusing student conflict in a special support classroom. Issue 3 (2nd September 2017) - Svahn, Johanna
Abstract: This article examines episodes of potential student conflict in a Swedish special support classroom in which teachers deploy a particular type of directive in the form of a negative imperative: 'bry dig inte' (Eng. 'don't mind …; don't bother …'). The analyses of three such extended episodes, by use of a conversation analytic approach, highlight how the focused directive works in a neutralising fashion in relation to students' affective stances, constructed through bodily displays (postures, facial expressions, gazes) and/or verbal acts (complaints, accusations, insults), explicitly offering an alternative way for involved students to avoid participating in an escalation of a conflict. A pertinent element of the analysed episodes is how the focused directive format appears to downplay the relevance of a conflict source, as well as be orienting more towards teaching students self-restraint than towards reprimand and punishment. The analysis also demonstrated how the directive seems to bear meta-pragmatic knowledge specific to the particular school culture, leading the connotation transmitted in the context to be more comprehensive than what follows from the actual words.